Analisis Dalam Pendukung Keputusan Seleksi Content Creator Mahasiswa Terbaik Menerapkan Metode EDAS dan ROC - Mesran Mesran; Dwina Pri Indini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
One of the uses of technology is social media, which is an application that can convey information to many people. Around 49 percent of Indonesia's population are active users of social media because the use of social media as a means of promotion is considered easier and more efficient to get a wider target audience. In creating content on social media, a quality content creator is needed. The selection of student content creators at Budi Darma University in Medan is important to be able to get students who are creative and have the potential to become social media content creators. In selecting content creators, students at Budi Darma University have several predetermined criteria, namely the number of social media, the number of tiktok followers, the number of Instagram followers, content production per day, content creativity and content design updates. In the process of selecting student content creators, a system is needed that can speed up and simplify the process of selecting student content creators, namely the SPK (Decision Support System). In this study the EDAS (Evaluation Based on Distance from Average Solution) method and the Rank Oder Centroid (ROC) method used are expected to help the selection process for accepting student content creators. So the best alternative to become a student content creator lies in alternative A8 on behalf of Arsyillah with a score of 182001